2011
DOI: 10.1163/156939311793898350
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Features and Classifiers for Classification of Early-stage Breast Cancer

Abstract: Microwave Imaging (MI) has been extensively investigated for a number of years to develop a technique to detect breast cancer at the earliest stages of development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 29 publications
2
41
0
Order By: Relevance
“…Applying feature extraction to the recorded data allows us to reduce the dimensionality of the data, thus we can minimize the processing of the input data by extracting only the essential components, and using these components for analysis with the classifier. In [28] it was shown that PCA was the best feature extraction method on average; additionally, when combined with the SVM classifier, it yielded the best results compared to the combination of other classifier and feature extraction methods. Thus, we adopt a similar methodology in this paper.…”
Section: Feature Extractionmentioning
confidence: 99%
“…Applying feature extraction to the recorded data allows us to reduce the dimensionality of the data, thus we can minimize the processing of the input data by extracting only the essential components, and using these components for analysis with the classifier. In [28] it was shown that PCA was the best feature extraction method on average; additionally, when combined with the SVM classifier, it yielded the best results compared to the combination of other classifier and feature extraction methods. Thus, we adopt a similar methodology in this paper.…”
Section: Feature Extractionmentioning
confidence: 99%
“…Two methods have principally been used for tumour modelling in 2D and in 3D studies: polygonal approximation using an elliptical baseline [44][45][46][47][48][49] and Gaussian Random Spheres [30,35,[50][51][52][53][54][55][56][57]. The basis for these methods is described in the following subsections.…”
Section: Tumour Modellingmentioning
confidence: 99%
“…UWB tumour classification was examined by Chen et al [44][45][46][47][48] and Teo et al [49] using tumours located in 2D breast models, while studies by Davis et al [30] and Conceição [51][52][53][54][55], McGinley et al [56], O'Halloran et al [57] and Alshehri et al [64] considered tumours in 3D breast models. The latter will not be further discussed in this study since discrimination between benign and malignant tumours is only assessed in terms of dielectric differences between the two types of tumours and does not address resulting tumour signatures due to different shapes, which is the scope of this paper.…”
Section: Combining Breast and Tumour Modelsmentioning
confidence: 99%
See 2 more Smart Citations